PENGARUH FAKTOR SPESIFIK BANK TERHADAP RISIKO KREDIT PERBANKAN PADA MASA PANDEMI COVID-19 - Amani Alhaura, Annisa; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The impact of the spread of the Covid-19 virus has affected the Indonesian banking sector, one of which is increasing credit risk. Therefore, this study aims to determine the effect of Income Diversification (DIV), Capital Adequacy Ratio (CAR), BOPO and Bank Size (SIZE) on Credit Risk (NPL) during the Covid-19 pandemic. The method of data analysis in this study uses the panel data regression method. The subjects in this study are banks that are included in the KBMI 4 category. The research data is sourced from the quarterly published reports of each bank from 2020:1 to 2022:3. The results of this study indicate that all independent variables can explain the dependent variable by 75.86% while the rest are influenced by other variables. Partially, income diversification has a negative effect on NPL. Capital Adequacy Ratio (CAR), and BOPO have a positive effect on NPL. Meanwhile bank size (SIZE) has no effect on NPL.